Motivations for Outward FDI from Emerging Economies to Advanced Economies: A Literature Review / Ibrahim Nandom Yakubu, Aziza Hashi Abokor and Iliasu Abdallah - Yakubu, Ibrahim Nandom; Abokor, Aziza Hashi; Abdallah, Iliasu (Universiti Teknologi MARA Shah Alam, 2020)
Outward Foreign Direct Investment (FDI) from emerging economies in recent years has experienced rapid growth, especially from the BRIC (Brazil, Russia, India, and China) economies. This has gained much attention from international business researchers. The present study assessed the motivations for the outward FDI from emerging economies to advanced economies based on literature review. The paper revealed that market seeking, natural resource seeking, strategic asset seeking, efficiency seeking, and home government support motivate firms from emerging economies to invest in advanced economies. However, efficiency seeking least motivates China's outward FDI due to its low labour cost. The study also made an evaluation of the existing theories of FDI to determine whether they adequately explain such investments. Based on the evaluation, the OLI Paradigm and the Resource- Based View do not adequately provide a plausible explanation for such investments. However, emerging economies outward FDI to advanced economies seemed to be adequately explained by the Institutional Theory.